Lithologo-facial, geochemical and sequence-stratigraphic sedimentation in Naunak suite (south-east Western Siberia) - Shaminova M. I. Marina Ivanovna; Rychkova I. V. Irina Vladimirovna; Sterzhanova U.; Dolgaya T. F. Tatiana Fedorovna (Stratigraphy and Regional Geology, 2014)
Title screen